Evaluation of Environmental Stressors Impact on Introducing Nuclear Power Plant in Bangka Island – Indonesia Using INPRO Methodology - Jupiter Sitorus Pane; Syahrir; Muhammad Budi Setiawan; Riesna Prassanti; Siti Alimah; Heni Susiati (Migration Letters, 2023)
As with other industrial activities, the construction and operation of a nuclear power plant (NPP) will impact the environment because of the changes in the environment within and around the activity location. According to the basic principle of the environment in the INPRO Methodology developed by the IAEA, the acceptability of expected adverse environmental effects arising from an NPP should be within the standard performance envelope for the NPP to be sustainable. Indonesia’s progressive development of its nuclear energy system (NES) involves a plan to build a 1000 MW NPP at the candidate site of Bangka Island. The environmental impact of this project was evaluated, including through a nuclear energy system assessment (NESA) using the INPRO Methodology to address long-term sustainability. One environmental impact analysis that needs to be considered is the release of stressors, in which controllability by optimizing actions will reduce the environmental impact of exposure to radioactive materials, toxic substances, and heat in the atmosphere and marine waters. The evaluation is aimed to ensure that the planned NES aligns with the existing NES in terms of controllability of environmental stressors, reduction of total environmental impact, and optimization of measures to mitigate environmental effects. The study concluded that the identified stressors are controllable within the regulatory limits, and effective measures are in place to control and reduce radiation-related effects. Hence, introducing a 1000 MW NPP in Bangka Island meets sustainability criteria from the environmental stressors impact point of view.